Fighting Corruption is a Guarantee of the Development of Society - Khaldorova Zuhra Fakhridinovna; Kasimova Zumrad Rahmatovna (Genius Journals, 2023)
The article analyzes the impact of corruption on the socio-economic and spiritual life of the society, the factors of its origin, and the mechanisms of combating it.
Keywords: corruption; crimes related to corruption; democracy; socio-political danger of corruption